Evaluasi Pengelolaan Limbah B3 Menggunakan Metode Evaluasi Skala Guttman pada Terminal Kalimas Tanjung Perak - Aflachul Risma Faradila; Syadzadhiya Qothrunada Zakiyayasin Nisa (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
As an integral part of Tanjung Perak Port, Kalimas Terminal holds a strategically important position in supporting Indonesia’s national export and import activities. Its vital role makes it one of the key logistics hubs in the country. During its operations, the generation of hazardous and toxic (B3) waste is unavoidable, requiring swift and proper handling to prevent environmental degradation and protect public health. This study aims to assess the level of compliance in B3 waste management at Kalimas Terminal, Tanjung Perak. The research focuses on evaluating key aspects such as the identification, collection, storage, and transportation of B3 waste, along with the completeness of related documentation, in accordance with applicable environmental regulations. By examining the current waste management practices in place, this study also seeks to formulate strategic recommendations to enhance the effectiveness and sustainability of B3 waste handling in the future.